Paragangliomas/Pheochromocytomas: Clinically Oriented Genetic Testing - Rute Martins; Maria João Bugalho (International Journal of Endocrinology)
Paragangliomas are rare neuroendocrine tumors that arise in the sympathetic or parasympathetic nervous system. Sympathetic paragangliomas are mainly found in the adrenal medulla (designated pheochromocytomas) but may also have a thoracic, abdominal, or pelvic localization. Parasympathetic paragangliomas are generally located at the head or neck. Knowledge concerning the familial forms of paragangliomas has greatly improved in recent years. Additionally to the genes involved in the classical syndromic forms: VHL gene (von Hippel-Lindau), RET gene (Multiple Endocrine Neoplasia type 2), and NF1 gene (Neurofibromatosis type 1), 10 novel genes have so far been implicated in the occurrence of paragangliomas/pheochromocytomas: SDHA, SDHB, SDHC, SDHD, SDHAF2, TMEM127, MAX, EGLN1, HIF2A, and KIF1B. It is currently accepted that about 35% of the paragangliomas cases are due to germline mutations in one of these genes. Furthermore, somatic mutations of RET, VHL, NF1, MAX, HIF2A, and H-RAS can also be detected. The identification of the mutation responsible for the paraganglioma/pheochromocytoma phenotype in a patient may be crucial in determining the treatment and allowing specific follow-up guidelines, ultimately leading to a better prognosis. Herein, we summarize the most relevant aspects regarding the genetics and clinical aspects of the syndromic and nonsyndromic forms of pheochromocytoma/paraganglioma aiming to provide an algorithm for genetic testing.